IMPROVED COMMUNICATION OF PARENTS AND TEACHERS BY USING ANDROID-BASED APPLICATIONS AS A MEDIA FOR FORMING CHARACTER CHILDREN AT AN EARLY AGE IN ELEMENTARY SCHOOL SD. TAMAN SARI 3 YOGYAKARTA - Wibawa; Widyastuti, Titik Mulat (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2019)
The process of character building for early childhood students is not optimal due to lack of communication between parents of students and teachers. This lack of communication  is caused by teachers' fear of being violating human rights when giving educational punishment or warning to students who have broken the school rules (are not disciplined). To overcome this problem there needs to increase communication between teachers and parents of students, so there is no misunderstanding of the information received. An android-based application is used to facilitate communication between parents and teachers. This application has facilities in the form of information on student violations records, activities at school, tasks that must be done at home, and the amount of attendance. By using the application, parents can monitor and be notified related in real time. The location of this research was conducted in elementary school. SD. Neg Taman Sari 3 Yogyakarta with research subjects are parents of students and class teachers and the total number of respondents was 35 people. This research was conducted using a descriptive method with a quantitative approach. Data collection techniques used were observation, interviews and documentation. The results of testing the effectiveness of communication between parents and teachers, and monitoring parents of their children's activities carried out before and after using the application. Data analysis using T Test using SPSS ver. 17, the result of the significance value (2-tailed) is 0,000 (p < 0.05). T test results showed a significant influence on communication problems. The results of the pretest and posttest Mathematics achievement scores with "Mean Paired Differences" obtained an average value of 7.5750 and 7.9953. This result is difference shows the influence of communication between teachers and parents of students.